Refused Derived Fuel RDF and its role in reducing production (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Refuse derived fuel (RDF) is considered one of the most important types of low cost thermal energy which can be tapped in the industry, especially the cement industry in particular being the need of high thermal energy during the production processes, and in this paper we have implemented the use of a derivative of the fuel RDF  as a substitute for gasoline , to reduce production costs and thereby achieve production efficiency, and the methodology used in this research statistical analysis as well as the use of the cost of kaizen target for the purpose of reducing costs and achieve production efficiency, and this has reduced the cost total cement production by which led to reduce total costs of cement production by 8.4% and an increase in production efficiency by 5.1% and this is a high percentage contribute to the improvement of the national economy if it has been applied in all cement plants on the level of Iraq as well as the disposal of waste in a healthy way And at a lower cost, also have been applying the kaizen target cost and led to lower the cost for each per ton of cement from $ 47.98 to $ 45.71 a closer as possible to kaizen target cost , which was $ 44 per ton, a good starting point for continuous improvement if what has been taking into consideration the rest of the negative influences that don’t add value can beeliminated gradually and with continuous improvement reaching the target cost.